Potret Pendanaan UMKM Berdasarkan Siklus Hidup Usaha - Maria Rio Rita (EBBANK, 2018)
The phenomenon of MSMEs is still interesting to discuss, especially from a financial perspective. One of the important financial decisions for a business is a financing decision. This decision will continue on investment decisions and the operationalization of daily business. This research was conducted at the batik UMKM located in Lasem, Rembang, Central Java. The sample selection process was conducted by purposive sampling method, 30 entrepreneurs were selected as respondents. The distribution of questionnaires and interviews was conducted to collect primary data. The data is processed using a qualitative descriptive method to describe the condition of MSME funding patterns based on their business life cycle. The results found that there were differences in the pattern of funding sources used by these MSMEs, both in cross section and time series. This study suggests a practical use of the firm life cycle model in helping MSME to understand how their financial decision is likely to adjust over time